Advantages and Recent Developments of Autologous Cell Therapy for Parkinson’s Disease Patients - Osborn, Teresia M.; Hallett, Penelope J.; Schumacher, James M.; Isacson, Ole (Frontiers in Cellular Neuroscience, 2020)
Parkinson’s Disease (PD) is a progressive degenerative disease characterized by tremor, bradykinesia, rigidity and postural instability. There are approximately 7-10 million PD patients worldwide. Currently, there are no biomarkers available or pharmaceuticals that can halt the dopaminergic (DA) neuron degeneration. At the time of diagnosis about 60% of the midbrain dopamine (mDA) neurons have already degenerated, resulting in a depletion of roughly 70% of striatal DA levels and synapses. Symptomatic treatment (e.g. with L-dopa) can initially restore DA levels and motor function, but with time often lead to side-effects like dyskinesia. Deep-brain-stimulation can alleviate these side-effects and some of the motor symptoms but requires repeat procedures and adds limitations for the patients. Restoration of dopaminergic synapses using neuronal cell replacement therapy has shown benefit in clinical studies using cells from fetal ventral midbrain. This approach, if done correctly, increases DA levels and restores synapses, allowing biofeedback regulation between the grafted cells and the host brain. Drawbacks are that it is not scalable for a large patient population and the patients require immunosuppression. Stem cells differentiated in vitro to mDA neurons or progenitors have shown promise in animal studies and is a scalable approach that allows for cryopreservation of transplantable cells and rigorous quality control prior to transplantation. However, all allogeneic grafts require immunosuppression. HLA-donor-matching, reduces, but does not completely eliminate, the need for immunosuppression, and is currently investigated in a clinical trial for PD in Japan. Since immune compatibility is very important in all areas of transplantation, these approaches may ultimately be of less benefit to the patients than an autologous approach. By using the patient’s own somatic cells, reprogrammed to induced pluripotent stem cells (iPSCs) and differentiated to mDA neurons immunosuppression is not required, and may also present with several biological and functional advantages in the patients, as described in this article. The proof-of-principle of autologous iPSC mDA restoration of function has been shown in parkinsonian non-human primates, and this can now be investigated in clinical trials in addition to the allogeneic and HLA-matched approaches. In this review, we focus on the autologous approach of cell therapy for PD.